Uncaria tomentosa for Reducing Side Effects Caused by Chemotherapy in CRC Patients: Clinical Trial. (21st August 2011) - Farias, I. L. G.; Araújo, M. C. S.; Farias, J. G.; Rossato, L. V.; Elsenbach, L. I.; Dalmora, S. L.; Flores, N. M. P.; Durigon, M.; Cruz, I. B. M.; Morsch, V. M.; Schetinger, M. R. C.
Abstract : To evaluate the effectiveness of Uncaria tomentosa in minimizing the side effects of chemotherapy and improving the antioxidant status of colorectal cancer (CRC) patients, a randomized clinical trial was conducted. Patients (43) undergoing adjuvant/palliative chemotherapy with 5-Fluorouracil/leucovorin + oxaliplatin (FOLFOX4) were split into two groups: the UT group received chemotherapy plus 300 mg of Uncaria tomentosa daily and the C group received only FOLFOX4 and served as a control. Blood samples were collected before each of the 6 cycles of chemotherapy, and hemograms, oxidative stress, enzymes antioxidants, immunologic parameters, and adverse events were analyzed. The use of 300 mg of Uncaria tomentosa daily during 6 cycles of FOLFOX4 did not change the analyzed parameters, and no toxic effects were observed.